2013
DOI: 10.1371/journal.pone.0064837
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Immature Myeloid Progenitors with Nitric-Oxide-Dependent Immunosuppressive Activity Isolated from Bone Marrow of Tumor-Free Mice

Abstract: Myeloid derived suppressor cells (MDSCs) from tumor-bearing mice are important negative regulators of anti-cancer immune responses, but the role for immature myeloid cells (IMCs) in non-tumor-bearing mice in the regulation of immune responses are poorly described. We studied the immune-suppressive activity of IMCs from the bone marrow (BM) of C57Bl/6 mice and the mechanism(s) by which they inhibit T–cell activation and proliferation. IMCs, isolated from BM by high-speed FACS, inhibited mitogen-induced prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…However, no difference was seen in the suppressive potential of MDSCs isolated from MM-bearing mice or healthy controls. In contrast to studies reporting that immature myeloid cells from naive mice are not immunosuppressive [14, 22], our results are in accordance with a report from Forghani et al who observed a comparable suppressive capacity for MDSCs isolated from the BM of tumor-free or mammary tumor-bearing mice, suggesting a physiological role of MDSCs in the control of T-cell proliferation and activation in the BM microenvironment [23]. Similarly, no significant difference was reported between the suppressive potential of MDSCs isolated from MM patients or healthy donors [16].…”
Section: Discussionsupporting
confidence: 92%
“…However, no difference was seen in the suppressive potential of MDSCs isolated from MM-bearing mice or healthy controls. In contrast to studies reporting that immature myeloid cells from naive mice are not immunosuppressive [14, 22], our results are in accordance with a report from Forghani et al who observed a comparable suppressive capacity for MDSCs isolated from the BM of tumor-free or mammary tumor-bearing mice, suggesting a physiological role of MDSCs in the control of T-cell proliferation and activation in the BM microenvironment [23]. Similarly, no significant difference was reported between the suppressive potential of MDSCs isolated from MM patients or healthy donors [16].…”
Section: Discussionsupporting
confidence: 92%
“…Our data indicate that the expression levels of immune checkpoint blockade molecules and Tregs varies dynamically over time and across different hematolymphoid tissues and organs in transplant recipients. Among transplant recipients with established GvHD, the expression levels and numbers of PD-1 and CTLA-4 positive donor T cells were higher in the BM than the spleen, consistent with a recent publication showing that the BM microenvironment is relatively immune-suppressive [ 39 ]. Host APCs surviving in the spleen and BM after lethal irradiation have been shown to play a pivotal role in activating allo-reactive donor T cells that cause GvHD [ 40 42 ].…”
Section: Discussionsupporting
confidence: 86%
“…Spleen and tumor suspension were stained with allophycocyanin (APC)-cyanine7 (Cy7)-conjugated anti-CD11b, fluorescein isothiocyanate (FITC)-conjugated Gr-1, and PE-conjugated lineage markers for 20 min at 4°C and FACS was performed as we have previously described [18].…”
Section: Cell Sortingmentioning
confidence: 99%
“…CD80, CD86, and MHC class II (I-A d ) expression levels were used to evaluate the maturation status of MDSCs [18,23]. Splenocyte-derived MDSCs from 4T1 tumor-bearing mice were co-cultured with Poly (I: C) (20 lg/ml) overnight.…”
Section: Poly (I: C) Influences Both Maturation and Suppressive Activmentioning
confidence: 99%
See 1 more Smart Citation